The Threat of Social Network Games in Indonesia: Ancaman Social Network Game di Indonesia - Sandy; Djoko Andoko; Poppy Setiawati Nurisnaeny; Mira Murniasari (Borneo Educational Journal (Borju), 2023)
This research examines the potential threat through SNG in Indonesia. The theories of threat, social media, cyber, and network society are used to analyze the research problem through qualitative analysis. Data was obtained through interviews and literature studies. The results of the study show that the potential threat on SNG includes ideological threats in society, growing illegal and pornographic content, theft of personal data, illegal monitoring of user activities, online fraud, cyberbullying, inappropriate content, dependence, and cyber attacks that threaten the activities of social network game users in Indonesia.